Social Inference May Guide Early Lexical Learning - Tripp, Alayo; Feldman, Naomi H.; Idsardi, William J. (Frontiers in Psychology, 2021)
We incorporate social reasoning about groups of informants into a model of word learning, and show that the model accounts for infant looking behavior in tasks of both word learning and recognition. Simulation 1 models an experiment where 16-month-old infants saw familiar objects labeled either correctly or incorrectly, by either adults or audio talkers. Simulation 2 reinterprets puzzling data from the Switch task, an audiovisual habituation procedure wherein infants are tested on familiarized associations between novel objects and labels. 18-month-olds outperform 14-month-olds on the Switch task when required to distinguish labels that are minimal pairs (e.g. "buk" and "puk"), but 14-month-olds’ performance is improved by habituation stimuli featuring multiple talkers. Our modeling results support the hypothesis that beliefs about knowledgeability and group membership guide infant looking behavior in both tasks. These results show that social and linguistic development interact in non-trivial ways, and that social categorization findings in developmental psychology could have substantial implications for understanding linguistic development in realistic settings where talkers vary according to observable features correlated with social groupings, including linguistic, ethnic and gendered groups.